Hubungan Dukungan Keluarga dengan Kualitas Hidup Pasien Diabetes Melitus Tipe 2 di Puskesmas Mangkang Semarang - Nur Mufid; Moch. Aspihan; Iskim Luthfa (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
Non-Communicable Diseases (NCDs) are major health problems that are influenced by genetic, physiological, environmental, and behavioral factors of individuals. One of the most common NCDs is Diabetes Mellitus (DM). Based on data from the Semarang City Health Office in 2023, there are 5,991 cases of DM that not only affect the elderly, but also adolescents, adults, and pre-elderly groups. This condition shows that type 2 DM is a serious challenge that affects the quality of life of sufferers. This study aims to analyze the relationship between family support and quality of life of type 2 DM patients at the Mangkang Semarang Health Center. The research method used is quantitative with a correlative descriptive design. A sample of 120 respondents was obtained through accidental sampling techniques, while data was collected by standardized questionnaires. The results showed that the average age of the respondents was 54 years old with the majority being female (55.2%) and having an elementary school education level (53.3%). The average family support score was 81.38, while the average quality of life of patients reached 86.15. This study concluded that patients with type 2 diabetes generally received good family support and had a positive quality of life. Furthermore, there is a positive relationship between family support and quality of life, where the greater the support provided, the more optimal the quality of life of type 2 DM patients.